2007
DOI: 10.1007/s11738-006-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytohormones on micropropagation of Artemisia vulgaris L.

Abstract: This paper describes an efficient in vitro micropropagation of Artemisia vulgaris using shoot tip and nodal explants. Among the various growth regulators tested, MS medium and B 5 vitamins supplemented with BA (4.44 lM) and KN (2.32 lM) combination was found to yield a better response than BA (4.44-13.32 lM) or KN (0.46-13.92 lM) alone in the medium. BA and KN combinations produced a maximum of 23.3 shoots per explant with 99.8% shooting frequency. Multiple shoots raised were elongated on MS medium containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 16 publications
6
22
1
Order By: Relevance
“…The petiole explant showed good response in direct organogenesis in MS medium fortified with 0.10 mg/l NAA + 0.75 mg/l TDZ. Similar results were obtained in Artemesia vulgaris (Sujatha and Kumari 2007). In the present study; petiole derived calli showed maximum shoot regeneration on MS medium supplemented with 0.10 mg/l NAA and 1.00 mg/l TDZ.…”
Section: Discussionsupporting
confidence: 90%
“…The petiole explant showed good response in direct organogenesis in MS medium fortified with 0.10 mg/l NAA + 0.75 mg/l TDZ. Similar results were obtained in Artemesia vulgaris (Sujatha and Kumari 2007). In the present study; petiole derived calli showed maximum shoot regeneration on MS medium supplemented with 0.10 mg/l NAA and 1.00 mg/l TDZ.…”
Section: Discussionsupporting
confidence: 90%
“…BAP has been described as a beneficial growth regulator for induction of shoots in other Artemisa species (Sujatha and Ranjitha Kumari 2007; Umer Sharief and Jagadish Chandra 1991). In Artemisia vulgaris it has been observed that shooting response was increased when BAP (4.44 lM) and Kn (2.32 lM) combination rather than BAP (4.44-13.32 lM) or Kn (0.46-13.92 lM) (Sujatha and Ranjitha Kumari 2007). In the present study, MS medium supplemented with BAP in combination with 2-iP yielded optimal shoot regeneration.…”
Section: Induction Of Multiple Shoots From Callussupporting
confidence: 49%
“…This cytokinin plays a significant role in shoot formation as it overcomes apical dominance and promotes axillary bud development (Xu, 2008). BA has been commonly used to induce shoot organogenesis in many plants, including species of the Asteraceae (Orlikowska et al, 1999;Sujata and Ranjitha Kumari, 2007;Chakrabarty and Datta, 2008). Our results confirm the findings of an earlier study comparing the effectiveness of BA, KN and ZEA, in which BA was found to be the most and zeatin the least effective (Shiva Pakash et al, 1994).…”
Section: Resultsmentioning
confidence: 99%